Pragmatic Experience with Risk-based versus Universal Hepatitis C Screening in Pregnancy: Detection of Infection and Postpartum Linkage to Care - Bushman, Elisa T.; Subramani, Lakshmi; Sanjanwala, Aalok; Dionne-Odom, Jodie; Franco, Ricardo; Owen, John; Subramaniam, Akila (American Journal of Perinatology, 2021)
Objective Despite the Centers for Disease Control and Prevention (CDC) and U.S. Preventive Services Task Force (USPSTF) recommending universal hepatitis C virus (HCV) screening in pregnancy Society for Maternal-Fetal Medicine (SMFM) and American College of Obstetricians and Gynecologists (ACOG) continue to endorse risk-based screening for HCV in pregnancy. We hypothesized that universal screening is associated with increased HCV diagnosis and postpartum linkage to HCV care compared with risk-based screening.Study Design This retrospective cohort study included pregnant women screened for HCV at a single tertiary-care center. We defined two cohorts: women managed with risk-based (January 2014–October 2016) or universal HCV screening (November 2016–December 2018). Screening was performed with ELISA antibody testing and viremia confirmed with HCV ribonucleic acid (RNA) polymerase chain reaction (PCR). Primary outcomes were the rate of HCV screen positivity and postpartum linkage to care.Results From 2014 to 2018, 16,489 women delivered at our institution, of whom 166 screened positive for HCV. A total of 7,039 pregnant women were screened for HCV: 266 with risk-based and 6,773 with universal screening; 29% (76/266) were positive HCV antibody screening (HCVAb + ) in the risk-based cohort and 1.3% (90/6,773) in the universal cohort. HCVAb+ women in the risk-based cohort were more likely to have a positive drug screen. Only 69% (62/90) of HCVAb+ women in the universal cohort met the criteria for risk-based testing. Of the remaining 28 women, 6 (21%) had active viremia (HCV RNA+). Of the 166 HCVAb+ women, 64% (103/166) were HCV RNA+—51 of 266 (19%) in the risk-based and 52 of 6,773 (0.8%) in the universal cohort. Of HCVAb+ women, 75% (125/166) were referred postpartum for HCV evaluation and 27% (34/125) were linked to care. Only 9% (10/103) of women with viremia initiated treatment within 1 year of delivery.Conclusion Universal HCV screening in pregnancy identified an additional 31% of HCVAb+ women compared with risk-based screening. Given low rates of HCV follow-up and treatment regardless of screening modality, further studies are needed to address barriers to postpartum linkage to care.Key Points
Keywords: Hepatitis C; pregnancy; screening; universal; risk based